GIS, GPS AND REMOTE SENSING APPLICATION TO INVESTIGATE AGRICULTURAL POTENTIAL IN CHOLISTAN - Farooq Ahmad (Sociedade & Natureza)
Agriculture plays the most important part in the economy of our country from macro perspective,while an equally important part in our social setup from a micro perspective. The ecologicalsystem of Cholistan desert is highly delicate and has gone under tremendous changes broughtupon by physical and mainly by human interventions. The rapid development and integrationof spatial technologies such as Geographic Information System, Global Positioning System,and Remote Sensing, have created many new tools for professionals, but have also widenedthe “digital divide”, leaving many with little understanding of the technology and potentialapplications. Remote sensing can provide valuable, timely and even predicted informationabout environment as an important basis for sustainable development. Geographic InformationSystem can provide effective tools for decision makers. The uses of GIS, GPS, and RS technologies,either individually or in combination, span a broad range of applications and degreesof complexity. It facilitates cooperative approaches and with the integration of GIS, there willbe a whole new framework for organizations and society to work together and make decisions.However, an integrated GIS based database management system handles this highly significanttask to make our country more prosper among Nations.